Analisis Roland Barthes : Representasi Budaya K-Pop dalam Iklan Lemonilo x NCT Dream - Andien Laksmi Febytasari; Riski Apriliani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Advertising is a digital communication tool that provides information to the public about a product. Besides projecting a positive image, advertising also provides information about lifestyle and culture. One such advertisement aired in Indonesia is for the healthy and practical noodle product, Noodles Lemonilo x NCT Dream. NCT Dream, a South Korean boy band, became the brand ambassador for the healthy noodle product in early 2022. This study aims to examine how Korean pop culture is represented in the Noodles Lemonilo x NCT Dream advertisement and to describe its semiotic meaning. This research employs a descriptive qualitative research method with Roland Barthes' semiotic theory analysis. Source triangulation was used to test the validity of the research. The object of this study was the Noodles Lemonilo x NCT Dream YouTube advertisement. Data collection techniques included visual observation through the YouTube advertisement, literature review, and documentation study. The researcher aims to prove that the Noodles Lemonilo x NCT Dream advertisement represents Korean pop culture through NCT Dream as the brand ambassador for the Noodles Lemonilo product and to obtain results from the semiotic meaning of the Noodles Lemonilo x NCT Dream advertisement.